DAMPAK PROGRAM YOUTH PARTNERSHIP PROJECT (YPP) OLEH ECPAT (END CHILD PROSTITUTION, CHILD PORNOGRAPHY AND TRAFFICKING OF CHILDREN FOR SEXUAL PURPOSES) DALAM MENANGANI KORBAN CHILD TRAFFICKING DI KAMBOJA PADA TAHUN 2009-2011 - Erlina Purnama Sari; Den Yealta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The Youth Partnership Project (YPP) is an ECPAT-based Program that is grounded to combat commercial sexual exploitation of children. And to empower children and youth to voice their own right to be protected and become leaders in combating commercial sexual exploitation of children.This study use a constructivist perspective. The essence of this theory is international politics consists in an intellectual effort to develop a theory of the international system as a